2021
DOI: 10.1089/cyber.2021.0043
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Vulnerability As a Determinant of Increased Risk for Cybersecurity Risk Behavior

Abstract: There is interest in better understanding people's cybersecurity (CS)-related attitudes and behaviors, which are ultimately impacted by their perceived vulnerability to CS risks. There is a relationship between how risk is perceived and how someone acts, with protection motivation theory (PMT) providing a particularly salient framework for explaining this connection. Exploration of how one perceives his or her own vulnerability to CS victimization is essential to understanding this interaction, and risk mitiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Research has found that the adoption of information technology by users is impacted by factors such as performance, privacy, and psychological risks [ 77 , 79 , 80 ]. For example, Debb found that people's attitudes and behaviours towards network security are related to their perception of network risks [ 81 ]. Chloe's research found that innovators, early adopters, and the early majority segments focus on performance risks in mobile payment adoption, while innovators, early adopters, and the late majority segments focus on security risks in mobile payment adoption [ 82 ].…”
Section: Conceptual Model and Hypothesesmentioning
confidence: 99%
“…Research has found that the adoption of information technology by users is impacted by factors such as performance, privacy, and psychological risks [ 77 , 79 , 80 ]. For example, Debb found that people's attitudes and behaviours towards network security are related to their perception of network risks [ 81 ]. Chloe's research found that innovators, early adopters, and the early majority segments focus on performance risks in mobile payment adoption, while innovators, early adopters, and the late majority segments focus on security risks in mobile payment adoption [ 82 ].…”
Section: Conceptual Model and Hypothesesmentioning
confidence: 99%
“…In addition, internal security threats are more difficult to detect and defend because of their strong concealment, direct harm and diversified means. The network defender undertakes the task of evaluating a large number of high-speed and heterogeneous streaming data 3 . In order to save manpower and time costs, how to find unknown threats and internal threats through existing multi-source data and logs has become a research hotspot 4,5 .…”
Section: Introductionmentioning
confidence: 99%